MMT spectroscopy of Lyman-alpha at z ≃ 7: evidence for accelerated reionization around massive galaxies. Issue 4 (15th February 2021) - Endsley, Ryan; Stark, Daniel P; Charlot, Stéphane; Chevallard, Jacopo; Robertson, Brant; Bouwens, Rychard J; Stefanon, Mauro
ABSTRACT: Reionization-era galaxies tend to exhibit weak Ly α emission, likely reflecting attenuation from an increasingly neutral IGM. Recent observations have begun to reveal exceptions to this picture, with strong Ly α emission now known in four of the most massive z = 7–9 galaxies in the CANDELS fields, all of which also exhibit intense [O iii ]+H β emission (EW > 800 Å). To better understand why Ly α is anomalously strong in a subset of massive z ≃ 7–9 galaxies, we have initiated an MMT/Binospec survey targeting a larger sample (N = 22) of similarly luminous (≃1–6 L $^{* }_{UV}$ ) z ≃ 7 galaxies selected over very wide-area fields (∼3 deg 2 ). We confidently (>7σ) detect Ly α in 78 per cent (7/9) of galaxies with strong [O iii ]+H β emission (EW > 800 Å) as opposed to only 8 per cent (1/12) of galaxies with more moderate (EW = 200–800 Å) [O iii ]+H β. We argue that the higher Ly α EWs of the strong [O iii ]+H β population likely reflect enhanced ionizing photon production efficiency owing to their large sSFRs (≳30 Gyr −1 ). We also find evidence that Ly α transmission from massive galaxies declines less rapidly over 6 < z < 7 than in low-mass lensed systems. In particular, our data suggest no strong evolution in Ly α transmission, consistent with a picture wherein massive z ≃ 7 galaxies often reside in large ionized regions. We detect three closely separated ( R = 1.7 physical Mpc) z ≃ 7 Ly α emitters in our sample, conceivably tracing a large ionized structure that is consistent with this picture. We detect tentative evidence for an overdensity in this region, implying a large ionizing photon budget in the surrounding volume.